Assessing the mycotoxicological risk from consumption of complementary foods by infants and young children in Nigeria - Ojuri, Oluwaseun T; Ezekiel, Chibundu N; Sulyok, Michael; Ezeokoli, Obinna T; Oyedele, Oluwawapelumi A; Ayeni, Kolawole I; Eskola, Mari K; Šarkanj, Bojan; Hajšlová, Jana; Adeleke, Rasheed A; Nwangburuka, Cyril C; Elliott, Christopher T; et al. (Food and chemical toxicology, 2018)
This study assessed, for the first time, the mycotoxicological risks from consumption of complementary foods by infants and young children in Nigeria. Molds belonging to Aspergillus aculeatinus, A. flavus, A. luchuensis, A. tubingensis, A. welwitschiae and Geotrichum candidum were recovered from the complementary foods. Twenty-eight major mycotoxins and derivatives, and another 109 microbial metabolites including chloramphenicol (a bacterial metabolite), were quantified in 137 food samples by LC-MS/MS. Aflatoxins and fumonisins co-contaminated 42% of the cereal- and nut-based food samples, at mean concentrations exceeding the EU limits of 0.1 and 200 μg/kg set for processed baby foods by 300 and six times, respectively. Milk contained mainly beauvericin, chloramphenicol and zearalenone. The trichothecenes, T-2 and HT-2 toxins, were quantified only in infant formula and at levels three times above the EU indicative level of 15 μg/kg for baby food. Chronic exposure estimate to carcinogenic aflatoxin was high causing low margin of exposure (MOE). Exposures to other mycotoxins either exceeded the established reference values by several fold or revealed low MOEs, pointing to important health risks in this highly vulnerable population. The observed mycotoxin mixtures may further increase risks of adverse health outcomes of exposure; this warrants urgent advocacy and regulatory interventions.
Keywords: Chromatography, Liquid; Infant Food; hodnocení rizik; Male; Mycotoxins; Exposure and risk assessment; Child, Preschool; Risk Assessment; zranitelné populace; Infant; tandemová hmotnostní spektrometrie; Infant nutrition; dietární expozice; Public health; mužské pohlaví; potrava pro kojence; referenční standardy; chromatografie kapalinová; nejistota; limita detekce; Nigérie; předškolní dítě; kontaminace potravin; lidé; ženské pohlaví; roční období; Seasons; Humans; Nigeria; kojenec; Uncertainty; Limit of Detection; Reference Standards; Vulnerable Populations; Complementary foods; Tandem Mass Spectrometry; Female; Dietary Exposure; Food Contamination; Child health; mykotoxiny